Angel's ink - Drake, Jocelynn (Asylum tales, 2012)
Looking for a tattoo and maybe a little something extra: a burst of good luck, a dollop of true love, or even a hex on an ex? Head to the quiet and mysterious Gage, the best skin artist in town. Using unique potions, a blend of extraordinary ingredients and special inks to etch the right symbol, he can fulfill any heart's desire. But in a place like Low Town, where elves, faeries, trolls, werewolves, and vampires happily walk among humanity, everything has its price. No one knows that better than Gage. Turning his back on his own kind, he left the magical Ivory Tower where cruel witches and warlocks rule, a decision that cost him the right to practice magic. And if he disobeys, his punishment, execution will be swift. Though he's tried to fly under the radar, Gage can't hide from powerful warlocks who want him dead or the secrets of his own past. But with the help of his friends, Trixie, a gorgeous elf who hides her true identity, and a hulking troll named Bronx, Gage might just make it through this enchanted world alive.